1991
DOI: 10.1016/0014-5793(91)80117-l
|View full text |Cite
|
Sign up to set email alerts
|

Stopped‐flow fluorescence kinetic studies of Glu‐plasminogen Conformational changes triggered by AH‐site ligand binding

Abstract: Bmdtnil of 6-ammohexaaolu acid tO the AH.I)Ie, a weak lyline bittdln8 lib: tn Glu,plasmlnoilen, =liters the conformation of tile moleculc~ The kmel. ice= of the blndlnii and the ac=:ompanylnil ¢onformational chanlle are investljated at pH 7 I!, 2.~'C Chanlle~ of lama,tie protein iluor~ccnee ~ete measured as a function of time after raped mixing in a stopped.flew app*ratus, The results reflect a two.step ra~¢tto,t meehan,sm. Rapid ass~iation of Glu.plasmtnogen and 6-ammohe~anoi¢ nod (K) =,44 raM) followed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 14 publications
4
19
0
Order By: Relevance
“…Cooperativity between binding sites was previously noted in plasminogen, the parent molecule of plasmin which contains similar binding sites ( Fig. 7 in [33], [35]); Takada et al also suggested mutual interactions between LBS in plasminogen [36]. A second phenomenon of positive co-operativity induced by oleic acid relates to the interaction of plasmin with the substrate S-2251 (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…Cooperativity between binding sites was previously noted in plasminogen, the parent molecule of plasmin which contains similar binding sites ( Fig. 7 in [33], [35]); Takada et al also suggested mutual interactions between LBS in plasminogen [36]. A second phenomenon of positive co-operativity induced by oleic acid relates to the interaction of plasmin with the substrate S-2251 (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…1 [13]) also is valid for each of the glycoforms individually. All other schemes previously considered [12, 13]cannot account for these data. Consequently, equation 2 of Scheme.…”
Section: Resultsmentioning
confidence: 99%
“…Small changes in the total fluorescence of glu-plasminogen (typically 10%) in the presence of lysine analogues or proteins are representative of lysine-dependent conformational changes to the zymogen (Christensen and Molgaard, 1991;Andronicos et al, 2000). Similarly, the change in total fluorescence of FITC-glu-plasminogen in the presence of MDA-MB-231 cells increased to a maximum of approximately 10% in a time-dependent manner ( Figure 1B).…”
Section: Stability and Conformation Of Cell Bound Plasminogenmentioning
confidence: 99%